Rozwój nauki w gorzowskim ośrodku Akademii Wychowania Fizycznego w Poznaniu w okresie 50 lat działalności uczelni (1971-2021) = The development of science at the Gorzow branch of the Poznań University of Physical Education during the 50 years of the institution`s operations (1971-2021) - Pilecka, Dorota; Jurek, Tomasz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the study was to address the following research question: What were the principal areas of scientific inquiry at the Gorzow Branch of the Poznań University of Physical Education over the 50 years of the institution`s history? In accordance with historical research methodology, analytical, synthetic, comparative, inductive, and deductive methods were employed. The study is based on existing sources and literature, with an in-depth analysis of the subject. All facts described underwent multiple rounds of verification, which consisted of several stages.
Keywords: gorzowska Filia AWF w Poznaniu; nauki o kulturze fizycznej; badania naukowe; Gorzow Branch of the Poznań University of Physical Education; physical culture sciences; scientific research